Shell occupation by the South Atlantic endemic hermit crab Loxopagurus loxochelis (Moreira, 1901) (Anomura: Diogenidae) - Frameschi, Israel Fernandes [UNESP] (2013)
The evaluation of population characteristics, particularly those of endemic species, aids in population preservation and management. Hermit crabs present an innate behavior of occupying shells, which tends to individual needs and limits their distribution. This study characterized the pattern of occupation of gastropod shells by the hermit Loxopagurus loxochelis in three bays of the southwestern coast of Brazil. Monthly collections were made from January/1998 to December/1999 in the bays Ubatumirim (UBM), Ubatuba (UBA) and Mar Virado (MV) with a shrimping boat. Overall, ten species of gastropod shells were occupied by L. loxochelis. The shell of Olivancillaria urceus represented 66.8% of those occupied. Morphometric relationships demonstrated a differential occupation of the more abundant shells among demographic groups, where most of the males occupied O. urceus, non-ovigerous females occupied O. urceus and Buccinanops cochlidium, and ovigerous females occupied B. cochlidium and Stramonita haemastoma. Most of the individuals occupied the more abundant shells, considered adequate for the morphology of this hermit crab species. Thus, the studied bays seem to be stable and propitious environments for population perpetuation and the settlement of new individuals.